Indigofera zollingeriana Leaf Extract Reduces Sheep Rumen Methane Production in Vitro - Suhartati, FM (ANIMAL PRODUCTION, 2020)
An experimental study aimed at assessing the reduction of gas methane production in thin-tailed sheep through the use of Indigofera zollingeriana leaf extract was conducted from May to September 2019 at Animal Nutrition and Feed Laboratory, University of Jenderal Soedirman Purwokerto. A One Way Classification of Completely Randomized Design (CRD) experiment was employed. The treatment included Indigofera zollingeriana leaf extract with levels of 0%, 0.40%, and 0.80% of feed dry matter and each treatment was repeated six times so that there were 18 experimental units. The feed provided consisted of 60% concentrate and 40% ammoniated rice straw. The concentrate consisted of coconut cake and rice bran with a ratio composition of 1:2. The material used was rumen fluid obtained from three thin-tailed sheep, sampled from the Sokaraja slaughterhouse immediately after the sheep were slaughtered. In vitro incubation was carried out for four hours. The variables measured included protozoan population, methane gas production and bacterial populations. The data obtained were then analyzed using analysis of variance and continued with the Orthogonal Polynomial test. The use of 0.80% Indigofera zollingeriana leaf extract can reduce the protozoan populations, methane gas production and can increase the bacterial populations of sheep rumen fluid.